2003
DOI: 10.1002/bem.10179
|View full text |Cite
|
Sign up to set email alerts
|

Microwave effects on the nervous system

Abstract: Studies have evaluated the electroencephalography (EEG) of humans and laboratory animals during and after Radiofrequency (RF) exposures. Effects of RF exposure on the blood-brain barrier (BBB) have been generally accepted for exposures that are thermalizing. Low level exposures that report alterations of the BBB remain controversial. Exposure to high levels of RF energy can damage the structure and function of the nervous system. Much research has focused on the neurochemistry of the brain and the reported eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(56 citation statements)
references
References 217 publications
(286 reference statements)
0
54
0
2
Order By: Relevance
“…Although most of the published papers on the biological effects of drugs in combination with RF exposure have been discussed elsewhere [D'Andrea et al, 2003;Adair and Black, 2003], a few papers with behavioral end points should be mentioned here. found that the increase in rat response rate on a fixed interval schedule produced by chlordiazepoxide was potentiated by exposure to 2450 MHz microwaves (1 mW/cm 2 ) even though the microwaves alone did not alter the trained behavior.…”
Section: Psychoactive Drug/microwave Interactionsmentioning
confidence: 99%
“…Although most of the published papers on the biological effects of drugs in combination with RF exposure have been discussed elsewhere [D'Andrea et al, 2003;Adair and Black, 2003], a few papers with behavioral end points should be mentioned here. found that the increase in rat response rate on a fixed interval schedule produced by chlordiazepoxide was potentiated by exposure to 2450 MHz microwaves (1 mW/cm 2 ) even though the microwaves alone did not alter the trained behavior.…”
Section: Psychoactive Drug/microwave Interactionsmentioning
confidence: 99%
“…The involvement of the nervous system in biological responses to RF-EMF is an extensively studied field [5,6] and lately, the implication of the peripheral nervous system in response to MMW has been highlighted, especially concerning modulation of the pain sensation [7].…”
Section: Introductionmentioning
confidence: 99%
“…2,9 D´Andrea et al (2003) 14 have reviewed studies about the possible non-thermal effects of mobile phone electromagnetic radiation on the electrical activity of the central nervous system (CNS). Results are controversial; some studies have found no electroencephalographic changes, while other have reported alterations in alpha and beta waves in humans, and delta waves in rats.…”
Section: Biological Effects Of Radiofrequency/microwavesmentioning
confidence: 99%
“…Results are controversial; some studies have found no electroencephalographic changes, while other have reported alterations in alpha and beta waves in humans, and delta waves in rats. 14 …”
Section: Biological Effects Of Radiofrequency/microwavesmentioning
confidence: 99%